2015
DOI: 10.1108/jeim-09-2013-0068
|View full text |Cite
|
Sign up to set email alerts
|

Information technology (IT) outsourcing by business process outsourcing/information technology enabled services (BPO/ITES) firms in India

Abstract: Purpose – The purpose of this paper is to understand the roles various drivers such as cost, strategy and risk play when business process outsourcing/information technology enabled services (BPO/ITES) firms in India outsource their information technology (IT) functions to third-party vendors. If all key drivers associated with IT outsourcing were understood, and such knowledge of those variables was incorporated into the reasons for outsourcing, there would be a greater probability of a success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…2.1, launching large-scale agile frameworks requires various changes in an organisation including different alterations in the way organisations source services. ITS strategy is also an aspect of sourcing which is on the one hand, more complex than any other types of sourcing (Patil and Wongsurawat 2015) and on the other hand, is mostly affected by the need to increase the speed and flexibility of agile frameworks (Dutta et al 2017;Gerster and Dremel 2019). As an example, incorporating agility impacts IT contract types (Zijdemans and Stettina 2014), since long and precisely specified contracts might be replaced by modules sourced in small and iterative packages (Opelt et al 2013).…”
Section: It Sourcing Within Agile Frameworkmentioning
confidence: 99%
“…2.1, launching large-scale agile frameworks requires various changes in an organisation including different alterations in the way organisations source services. ITS strategy is also an aspect of sourcing which is on the one hand, more complex than any other types of sourcing (Patil and Wongsurawat 2015) and on the other hand, is mostly affected by the need to increase the speed and flexibility of agile frameworks (Dutta et al 2017;Gerster and Dremel 2019). As an example, incorporating agility impacts IT contract types (Zijdemans and Stettina 2014), since long and precisely specified contracts might be replaced by modules sourced in small and iterative packages (Opelt et al 2013).…”
Section: It Sourcing Within Agile Frameworkmentioning
confidence: 99%
“…The restaurant industry is no exception (Collins et al , 2017; DeMicco et al , 2015). Previous studies have shown that companies that invested in information technology (IT) were able to achieve revenue growth as well as cost savings (Kauffman and Walden, 2001; Kulatilaka and Venkatraman, 2001; Patil and Wongsurawat, 2015; Ruth et al , 2015; Sambamurthy et al , 2003). As a result, “with the advent of new technology and its impact on restaurant operations, one would believe that most firms in the restaurant industry would be IT-oriented in the production and delivery of goods and services” (Oronsky and Chathoth, 2007, p. 942).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it became necessary to study the possibility of identifying business processes and determining their importance for the formation of a value chain and competitiveness. The concept of a "business process" we propose to use what is defined in the ISO 9000 standard, where the process is treated as a "set of interrelated and interacting operations (actions) that convert inputs to outputs" [7].…”
Section: Main Bodymentioning
confidence: 99%